MARKETING STRATEGY IN ATTRACTING CONSUMERS PURCHASE INTEREST IN PANDEMIC (Case Study Café in Rengat) - Fransinatra, Ziko; Asmara, Bima Sandi; Gustika, Gita Sari (JURNAL MANAJEMEN DAN BISNIS, 2021)
The application of marketing strategies within the company is very influential in the performance of the company concerned. The success or failure of the company is largely determined by how developed by the company to be able to compete for consumers in the implementation of an effective marketing strategy. Cafes that will be observed were located in Rengat. The choice of the objects because they have been existed until today, even though the Pandemic rises. Furthermore, The marketing strategy itself is a plan for implementing and controlling activities aimed at influencing exchanges in order to achieve organizational goals. Developing and implementing a marketing strategy, one of the stages is planning a marketing mix consisting of four elements, namely product, price, distribution/place, and promotion. Consumers are one of the most decisive elements. On the marketing variable, the Cafes should reconsider the amount of costs offered for sales, and managers should pay attention to the comfort of the consumers and increase promotion to get stability number of sales during pandemic. it is also necessary to take a stance to make improvements to previous program failures in achieving future targets. Cafes’ managers need to formulate short-term, medium-term and long-term goals so that it needs to strive to build positioning in the community. On the marketing variable, as a result, pandemic is not a reason to sustain the business. This study aims to determine the marketing strategy in attracting consumers used by them and to determine whether the marketing strategy used to attract consumer interest. The type of research carried out is field research (field research), is descriptive. The results of this study indicate the influence of Cafés Managers marketing strategy to survive during this pandemic.